PENGARUH MODEL PEMBELAJARAN KOOPERATIF TEKNIK TWO STAY TWO STRAY (TSTS) DAN AKTIVITAS BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS VII DI SMPN 1 PANJI SITUBONDO - Guretno Guretno (Jurnal Penelitian dan Pendidikan IPS, 2015)
This research aims to know the influence of cooperative learning Two Stay Two Stray (TSTS) and learning activity on learning achievement of seventh graders at SMPN 1 Panji Situbondo. Ninety two (92) students were invoked as respondents. As the result, there are partial influences on TSTS, learning activities and TSTS and learning activity simultaneously of leaning achievement.